2020
DOI: 10.1186/s12879-020-4907-1
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed HIV, hepatitis B, and hepatitis C infections in people with severe psychiatric disorders in Ethiopia

Abstract: Background: Worldwide, there is limited epidemiologic evidence on the seroprevalence of undiagnosed chronic viral infections including HIV, hepatitis B virus (HBV) and hepatitis C virus (HCV) infections among patients with severe psychiatric disorders. To our knowledge, this is the first study to explore and compare undiagnosed seroprevalence rates of HIV, HBV, and HCV infections among patients with severe psychiatric disorders. Method: In this study, we included a random sample of 309 patients with severe psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…28 Universal screening paradigms would likely reduce experienced stigma, and have high acceptability among people with SMI, with consent rates ranging between 57.0% and 96.6% in cross-sectional studies. 23,29,30 HCV screening by frontline clinicians could be prompted by novel integrated strategies like alerts on EMR and supported by HCV education programmes. This could be coupled with prompts for follow-up tests and specialist referral, especially among individuals with detected or known HCV seropositive, and in doing so, could ameliorate attrition in the care cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Universal screening paradigms would likely reduce experienced stigma, and have high acceptability among people with SMI, with consent rates ranging between 57.0% and 96.6% in cross-sectional studies. 23,29,30 HCV screening by frontline clinicians could be prompted by novel integrated strategies like alerts on EMR and supported by HCV education programmes. This could be coupled with prompts for follow-up tests and specialist referral, especially among individuals with detected or known HCV seropositive, and in doing so, could ameliorate attrition in the care cascade.…”
Section: Discussionmentioning
confidence: 99%
“…As a starting point, once‐off lifetime BBV screening with subsequent risk‐based screening should be adopted in SMI populations, in alignment with recent general population screening policy promulgated by the US Centre for Disease Control 28 . Universal screening paradigms would likely reduce experienced stigma, and have high acceptability among people with SMI, with consent rates ranging between 57.0% and 96.6% in cross‐sectional studies 23,29,30 . HCV screening by frontline clinicians could be prompted by novel integrated strategies like alerts on EMR and supported by HCV education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent meta-analysis that assessed the prevalence of migraine headaches among patients with bipolar disorder involving seven studies on the subject found that roughly one-third of patients with bipolar disorder had comorbid migraine headaches (30.36%) [8]. However, the existing literature indicates that: (1) the vast majority of co-occurring medical conditions were untreated and undertreated; (2) most of them remain undiagnosed [10]; (3) even among those patients receiving treatment, the quality of service/care for both the comorbid medical condition and psychiatric disorders has been inadequate [11,12]. Scientific evidence shows that early identification and treatment of comorbid medication conditions in patients with severe psychiatric disorders are associated with improvement in outcomes, increased quality of life, reduced burden and cost associated with medical services, and improved in functionality/productivity [13,14].…”
Section: Introductionmentioning
confidence: 99%